2005
DOI: 10.1038/sj.eye.6702073
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the reproducibility and repeatability of a method of grading macular subretinal fluid using optical coherence tomography

Abstract: Aim To devise a quantative method for the measurement of the extent of macular subretinal fluid using optical coherence tomography (OCT), and to assess the interobserver and intraobserver agreement for this grading system. Methods Observational cohort series. Patients were a cohort who underwent retinal detachment surgery over an 18-month period. All patients had OCT scan at 6 weeks after surgery. The scans were graded by two independent observers experienced in OCT interpretation and each grader was masked to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…A final limitation is that we did not specifically investigate the repeatability of our measurements. However, the repeatability for these measurements was reported previously and was shown to be excellent [26,27,28].…”
Section: Discussionmentioning
confidence: 59%
“…A final limitation is that we did not specifically investigate the repeatability of our measurements. However, the repeatability for these measurements was reported previously and was shown to be excellent [26,27,28].…”
Section: Discussionmentioning
confidence: 59%
“…Repeat injections were given in the presence of persistent leakage or recurrence of retinal oedema. Clinical evaluation included log MAR or Snellen acuity, complete ophthalmic examination, optical coherence tomography (OCT), 3 and fluorescein angiography (FA). Ethics Committee approval was obtained for this study.…”
Section: Methodsmentioning
confidence: 99%
“…Unfortunately, the resolution of ultrasound is not as high as the OCT Ophthalmoscope, and it would be difficult to measure the volume of the subretinal fluid in cases of CSC or AMD by ultrasonography. Benson et al (2006) reported on a method of grading the area of subretinal fluid using the six OCT B scan images, but they did not calculate the volume of the subretinal fluid. The vertical cursor line had a step-like pattern (see green vertical line of Figure 5) after we moved the horizontal cursor line, and this must introduce a small amount of error.…”
Section: Discussionmentioning
confidence: 99%
“…In these studies, the actual volume was not measured (Montero et al. , 2003; Abouzeid and Wolfensberger, 2006; Benson et al. , 2006).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation